X-ray examinations of atypical femoral fractures - Schilcher, Jörg; Wang, Chunliang (AIDA Data Hub, 2021)
Atypical femoral fracture is a well-documented adverse reaction to bisphosphonate treatment, but may also have other causes. This dataset contains 433 radiographs from 149 patients with complete AFF, and 549 radiographs from 224 patients with normal femur fractures. There are no diagnoses of cancer, to reduce the risk of confounding by indication.
Keywords: Radiology; X-ray; Annotated; Femur; AFF; Atypical femoral fracture; Medical and Health Sciences; Medicin och hälsovetenskap; Radiology and Medical Imaging; Radiologi och bildbehandling